PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN PELAPORAN SERTA IMPLIKASINYA TERHADAP KUALITAS LABA - Nera Marinda Machdar (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
The purpose of this study is to test empirically whether is a significant effect between firm characteristics on the reporting disclosure, a significant effect between firm characteristics on the reporting disclosure through earnings quality, and a significant effect between the reporting disclosure on earning quality. to measure earnings quality, this study uses the Dechow and Dichev model (2002). Results of the study are that there is no relationship between firm characteristics with the reporting disclosure, exxept the size of the company; there is no relationship between firm characteristics and earnings quality through the reporting disclosure, and there is no relationship between the reporting disclosure with earnings quality.